Development and Evaluation of Vaginal gel Containing Ketoconazole in Combination with Probiotic Bacteria - Priti Balasaheb Shinde, Ankit Singh, Amit Kasabe (South Eastern European Journal of Public Health, 2025)
Ketoconazole an imidazole derivative has been mainly used for treatment of vaginal candidiasis. The identity of Ketoconazole was confirmed by UV spectrophotometric and IR analysis. The identity, purity, viability and stability of Lactobacilli species was confirmed by various macroscopic, microscopic and chemical tests. The gel formulations were characterized by their physical and performance tests. Polymers from both the classes (semi synthetic and synthetic) were selected on the basis of their viscosity, spreadability. The selected formulations were further characterized for suitability using appearance, viscosity, spreadability, pH and drug content, bioadhesive strength and in-vitro drug release. Only those formulations which indicated the prolonged release of Ketoconazole from the preformed gels over period of 7 hrs were short listed for determining antifungal efficacy of formulation, animal study and stability study. The antifungal efficacy of Ketoconazole was comparable with marketed vaginal gel formulations. The selected formulations were not affected much when stored at 50C and 250C over 45 days. At 400C, slight decrease in viscosity and drug content was observed. The topical vaginal gel formulation did not produce any dermal toxicity in the rabbits.